(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article examines one of the most significant branches of musical art — jazz. Particular attention is paid to the historical prerequisites for the emergence of jazz, its stylistic diversity, and the artistic features of performance. Improvisation, as a key principle, has led to the formation of more than forty independent styles within jazz, each reflecting the spirit of its era, its social environment, and the individuality of performers. The author analyzes the main jazz styles, their distinctive characteristics, prominent representatives, and the influence of jazz on the development of world musical art.